The effect of mechanical properties on polymer deformation and flow suspension in the selective laser sintering process - Belgada, Rihabe; Zarbane, Khalid; Mzerd, Ahmed (Zielona Góra: Uniwersytet Zielonogórski)
Among the various additive manufacturing processes, there is selective laser sintering, with the use of a high-power laser that sinters the small particles of polymer powder and turn them into a solid structure, from a 3D model, nowadays SLS additive manufacturing has become the best choice for the industry, especially for polymer materials, SLS ensures high productivity and well-honed materials at low cost.
Keywords: additive manufacturing; small polymer; selective laser sintering; suspension of polymer granule; flow deformation